A Game Theory Approach for Supply Chain Coordination Model with Incentive Mechanisms of Discount and Delay in Payments - Mohammad Ferdousmakan; Roya M. Ahari; Mohammadreza Vasili; Majid Vaziri Sarashk (Discrete Dynamics in Nature and Society)
The uncertain nature of supply chains is one of the key challenges managers, and researchers encounter in decision-making. Accordingly, this paper proposes a three-echelon supply chain in which demands are uncertain. The proposed supply chain has three participants, including supplier, manufacturer, and retailer, while three decentralized, centralized, and coordination models have been formulated to maximize participants’ profits. In the decentralized model, both the manufacturer and retailer independently determine the level of investment and order quantity regarding scenario-based demands. The centralized model determines the optimal order quantity and investment amounts for the whole network. However, these amounts may be different from optimal values for all participants. As such, using game theory, a bilevel adjustable contract based on wholesale price has been proposed as an incentive for players to participate in the coordination plan. Results show that the coordination model outperforms others by reducing the network’s costs and increasing profits simultaneously.